HIV pre-exposure prophylaxis adherence among female sex workers in Mutare urban, Zimbabwe - Mhlanga, Maxwell; Emillia Mutya, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Pre-exposure prophylaxis (PrEP) for HIV is a strategy that has been recently engineered to prevent individuals who are human immunodeficiency virus (HIV)-negative but are at high risk of being infected with HIV. Sex workers are one of the vulnerable groups that are targeted by PrEP, however effectiveness of PrEP is realised when there is maximum adherence. Empirical evidence from Mutare Urban district revealed that for the period April to November 2019, the adherence rate was 22 % (NAC, 2019).Therefore, this study sought to unearth the reasons why sex workers were not adhering to PrEP. A 1:1 unmatched case-control study was carried out in Mutare urban. The source population of this study was all female sex workers registered under NAC key population programs in two sites namely Forbes and Sakubva residing in Mutare urban. A total sample size of 64 participants calculated using Epi info 7 was used for this study. Participants were identified from records at the study sites and systematic sampling was done for both controls and cases.  Proportional selection of participants was done for the two centres. Data was collected using an interviewer administered structured questionnaire and a key informant interview guide was used to interview health service providers. Data was analysed using Epi info version 7. A multivariate analysis showed age [AOR = 2.14, 95% CI (1.08 – 3.34)], household expenditure per month [AOR = 18.77, 95% CI (3.13 – 11.21)], consistent use of condoms [AOR = 11.78, 95% CI (1.03 – 13.41)], alcohol use [AOR = 2.55, 95% CI (1.01 –5.32)], experienced side effects [AOR = 16.06, 95% CI (5.71 – 22.56)] and satisfaction with health service provision [AOR = 10.01, 95% CI (2.32 – 43.25)] to be statistically significant predictors of uptake of PrEP services. There is need for tailor made interventions for young sex workers, furthermore use of mobile applications to remind clients, provision of safety nets and continued health education to both the female sex workers and the community at large to reduce stigmatization.